Feeling the Scope of Solidarity: The Role of Emotions for Volunteers Supporting Refugees in Germany - Karakayali, Serhat (Social Inclusion, 2017)
In recent political debates in Germany, volunteers and citizens who support the cause of refugees are often accused of being "too emotional". Based mainly on empirical evidence from 10 group discussions and 35 individual interviews with volunteers, conducted in 2016, this article undertakes a sociological analysis of the role of emotions for volunteers.